Síntese, caracterização e avaliação in vivo e in vitro da biocompatibilidade de nanocristais de TiO2 - Brito, Patrícia de Freitas Leucas (2013)
Upon the current need for research with TiO2 nanocrystals (TiO2 NCs) properly characterized in order to evaluate their biological effects, this work was done aiming to synthesize and characterize TiO2 NCs, and evaluate their biocompatibility. The nanoparticles were synthesized by the precipitation in aqueous solution technique, and characterized by the techniques of X-ray diffraction, micro-Raman and spectrophotometry. To evaluate the biocompatibility, TiO2 NCs were tested in vivo using subcutaneous implants using Balb/c mice at a dose of 1g/kg for 15, 30 and 90 days for later histological analysis of the groups of 15 and 90 days and transmission electron microscopy of the group 30 days. In vitro evaluation consisted of cell viability assays, detection and measurement of nitric oxide metabolites and measurement of cytokine production in situ and in cultured macrophages challenged with different concentrations of TiO2 NCs. Cell viability was assessed after 72 hours by the MTT colorimetric assay, using five different concentrations of a solution of 10μg/ml, 20μg/ml, 40μg/ml, 100μg/ml and 200μg/ml in culture challenge of peritoneal macrophages Balb/c mice with 2, 12, 24 and 72 hours. From the supernatant of cultures of peritoneal macrophages was evaluated the production of nitrite by the Griess method and dosage levels of TNF-α, IL-1β, IL-12, IFN- and IL-4 by ELISA. The same technique was used for the determination of cytokine levels obtained from subcutaneous tissues underwent implantation of TiO2 NCs. After analysis of the data distribution by Kolmogorov-Smirnov test, we proceeded to their analysis by the Kruskal-Wallis test with Bonferroni post-test. The experiments of synthesis and characterization resulted in TiO2 nanocrystals of 8.5 nm on average, mixed phase, high purity level and quantum confinement effects. Histological analysis of the 15 days group showed a intense granulomatous nonspefic type inflammatory response with signs of necrosis and hemorrhage, which progressed with a slight reduction in its intensity, observed especially at 90 days of observation. Presence of clusters of nanocrystals with macroscopic dimensions, surrounded by macrophages and multinucled giant cells forming granulomas with fibrous capsules, which could be regarded as a typical reaction of granulomatous foreign body type and more intense fibrosis formation at 90 days within the material deployed. Nanocrystals were identified in lymph nodes in the different periods of study, suggesting that these particles might be transposed. Electron microscopy confirmed the evidence of apoptosis and vacuolar degeneration. The MTT test resulted in 40% viable cells in only 10 and 20μg/ml. The in vitro cytokine assay showed that there was not a tendency dose or time-dependent samples, presenting different behavior of TNF-α, IL-1β, IL-12 and increased production of IFN- probably due to low production of IL -4. The nitrite production was higher in the samples of 10μg/ml. The production of all cytokines in vivo experiment by the 15 days group was enhanced, decreasing in a time-dependent fashion, collaborating with the findings in vivo. We conclude that the TiO2 nanocrystals present in the tested concentrations presented inflammatory effects in vivo, cytotoxic and inflammatory conditions in vitro. These findings show that the experimental conditions studied NCs are not biocompatible.